Symptomatic menopause: Additional challenges for incarcerated women. (August 2021) - Schach, Eliana; Kothari, Jaineel; Perkiss, Evan; Hutchinson-Colas, Juana; Turock, Heather; McGreevey, James; Bachmann, Gloria; ,
Highlights: Menopausal women who are incarcerated are at increased risk of having a more adverse menopausal experience than non-incarcerated ones. Prison itself adversely affects quality of life, due to confinement, societal stigma and the absence of family. Incarcerated menopausal women tend to be at increased risk of exacerbation of depressive and anxiety symptoms, which they are already at risk for when in prison. These mental health issues are also directly related to vasomotor symptoms, night sweats, and interrupted sleep patterns. Resources should be made available for more comprehensive medical care of incarcerated women, including hormonal therapy when indicated. Abstract: Menopause is an age-associated physiological transition in women, usually occurring between the ages of 40 and 58 years, with an average of 51 years. As the age of women residing in the prison system is increasing globally, it becomes increasingly important for older female inmates to be assessed for menopausal symptoms and offered effective, personalized management. Middle-aged and older women, regardless of their living situation, are at increased risk of experiencing vasomotor symptoms and developing pelvic floor problems, bladder dysfunction and osteoporosis. However, all of these menopausal sequelae are typically exacerbated by prison conditions and by a lack of health support. Therefore, it is critical to implement prison programs and to create gender-specific training to aid in the health care needs of aging female inmates. Addressing this growing population of incarcerated women and attending to their menopausal needs require advocacy and active monitoring of prison-specific templates of care to ensure quality care. One such initiative legislated to address the health care needs of incarcerated women was commenced in New Jersey, USA. This entity, the NJ Commission on Women's Reentry, is addressing the unique health care needs of women, including menopausal ones, while incarcerated and then upon reentry into their community.